Species composition and distribution of mollusca on dead coral from Central to North Vietnam - Hua, Thai Tuyen; Phan , Thi Kim Hong; Nguyen, An Khang; Mai, Xuan Dat; Nguyen, Trung Hieu; Nguyen, Ngoc Anh Thu (Vietnam Journal of Marine Science and Technology, 2023)
A study on Mollusks’ species composition and distribution on dead coral from Quang Ngai to Cat Ba was conducted during the field survey between Vietnam and Russia on the AKADEMIC OPARIN RC vessel in 2021 at 39 reef stations in 14 study areas. By comparative morphology method, the authors have identified 135 taxa of Mollusca belonging to 48 families, 4 classes on coral reefs. The species composition of Mollusca was slightly different between study areas.